A low voltage micropower digital Class D amplifier modulator for hearing aids - Adrian, Victor (2010)
We present a micropower digital modulator for class-D amplifiers for power-critical digital hearing aids. The modulator design embodies a proposed Lagrange interpolation (a combined first- and second-order Lagrange) algorithmic pulsewidth modulation (PWM) and a third-order DeltaSigma noise shaper. By means of double-Fourier-series analysis, we analyze and determine the harmonic nonlinearities of the proposed algorithmic PWM. At 48-kHz sampling, 96-kHz PWM output, 997-Hz input, and input modulation index=0.9, the modulator circuit achieves a total harmonic distortion + noise (THD + N) of - 74dB (0.02%) over an 8-kHz voice bandwidth-12-dB THD + N improvement over a reported design and yet dissipates only ~ 50% of the power. The proposed modulator dissipates the lowest power dissipation of all modulators compared, and by means of a proposed figure of merit, the proposed modulator exhibits very competitive performance. The modulator IC is fabricated in a 0.35-mum digital CMOS process with a core area of 0.46 mm2.